Levels, Trends and Determinants of Tobacco Quitting Behaviour in India: Findings from Two Consecutive Nationally Representative Surveys - Shailja Sharma; Harshvardhan Singh; Jayanta Kumar Bora; Yuvaraj Krishnamoorthy; Nidhi Jaswal; Sonu Goel (Preventive Medicine: Research & Reviews, 2024)
Introduction: Quitting tobacco use is known to decrease mortality by 90% if successfully achieved before middle age. This analysis was conducted to assess the levels, trends and determinants of tobacco quitting behaviour amongst the Indian population. Materials and Methods: This was secondary data analysis of the National Family Health Survey (NFHS)-4 (2015–2016) and NFHS-5 (2019–2020) of India. Results: A rising trend (4%) in intention to quit tobacco was observed amongst women, while a decline in intention to quit (0.5%) was observed amongst men from 2015–2016 to 2019–2020. An increase in the quitting was observed amongst women with age, with higher levels of education, being married or widowed/separated/divorced, hypertensives and diabetic patients. Amongst men, a declining trend to quit was observed with increasing level of education amongst the richest and amongst smokers, alcohol users and diabetics. The trends in quitting increased amongst those who were exposed to mass media. Conclusion: This study shows an increase in tobacco quitting amongst females and a decline amongst men in the Indian population from 2015–2016 to 2019–2020.